Determination of active radical scavenging compounds in polar fruit and vegetable extracts by an on-line HPLC method. Issue 1 (June 2015) - Van Der Werf, Remmelt; Dal, Stéphanie; Le Grandois, Julie; Aoude-Werner, Dalal; Digel, Fabien; Ennahar, Said; Sigrist, Séverine; Marchioni, Eric
Abstract: Fruit and vegetables are believed to help fight against oxidative stress, given their natural content in radical scavenging compounds. Natural polyphenols neutralize reactive oxygen species by means of electron and hydrogen atom transfers. An HPLC method, hyphenated with a post-column reaction system relying on ABTS + bleaching assay was applied in order to quantify the chemical activity of radical scavenging compounds in red cabbage, onion, quince, sweet cherry, strawberry, carrot and tomato. Hyphenated to the ABTS + post-column reaction system, this method showed high antioxidant capacity notably in cherry, quince, onion, or red cabbage. Structural analysis of the compounds of interest showed the implication of several cyanidins and caffeoylquinic acids in cherry. Quince and red cabbage were found highly active through the presence of respectively caffeoylquinic acids, and an important content of diverse cyanidins variously glycosylated and acylated. The onion extract revealed a chemical core structure (quercetin) responsible for its antioxidant capacity. Moreover, our results showed that depending on the glycosylation profile of these compounds, their radical scavenging capacity can be very different. Highlights: On-line HPLC-antioxidant capacity method with a wide application within complex food samples. High variety of cyanidin derivatives confers substantial antioxidant capacity in red cabbage. A single quercetin derivative confers highest radical scavenging activity to onions. Glycosylation patterns seem to be determinant in terms of radical scavenging capacity (i.e. quercetin).